The natural statin α,β-dehydromonacolin K exerts anti-secretory effect in human intestinal epithelial cells via a nonsense-mediated mRNA decay-dependent mechanism - Saravut Satitsri; Rungtiwa Khumjiang; Chittreeya Tansakul; Wararat Chiangjong; Nuttapon Apichaiyarat; Taya Kitiyakara; Yanisa Purintrapibal; Vatcharin Rukachaisirikul; Chatchai Muanprasat (Pharmaceutical Biology)
Context cAMP-induced intestinal chloride secretion plays a pivotal role in the pathogenesis of secretory diarrheas.Objective In this study, we investigated the antisecretory effects of α,β-dehydromonacolin K, a derivative of lovastatin from Aspergillus sclerotiorum, on cAMP-induced chloride secretion in human T84 cells and fluid secretion in human colonoids.Materials and Methods Short-circuit current analyses and swelling assays were used to investigate the effects of α,β-dehydromonacolin K on chloride transport and fluid secretion, respectively. Proteomic analyses were performed to determine the potential anti-diarrheal mechanisms of α,β-dehydromonacolin K.Results In T84 cells, α,β-dehydromonacolin K inhibited cAMP-induced chloride secretion with an IC50 of ∼ 6.32 μM. Apical chloride current analyses demonstrated that α,β-dehydromonacolin K inhibited CFTR chloride channels stimulated by cAMP agonists with an IC50 of ∼ 1 μM. Basolateral potassium current analyses indicated that α,β-dehydromonacolin K had no effect on basolateral potassium channel activities. In a three-dimensional (3D) model of human colonoids, α,β-dehydromonacolin K (20 µM) suppressed both cAMP-induced and calcium-induced fluid secretion by ∼ 70%. Proteomic analyses of human colonoids revealed that α,β-dehydromonacolin K interacted with 33 proteins, including those associated with non-sense-mediated mRNA decay (NMD). Notably, the inhibitory effects of α,β-dehydromonacolin K on cAMP-induced chloride and fluid secretion were significantly diminished in the presence of SMG1i, an inhibitor of serine/threonine-protein kinase SMG1 involved in NMD, suggesting that α,β-dehydromonacolin K inhibits cAMP-induced chloride-driven fluid secretion in human intestinal epithelial cells by mechanisms involving SMG1-dependent NMD pathways.Discussion and conclusions α, β-Dehydromonacolin K represents a promising class of natural compounds that exert antisecretory effects in human intestinal epithelia via a novel mechanism of action involving SMG1 in NMD pathways.